PENURUNAN KEKUATAN TANAH TERSTABILISASI PALM OIL FUEL ASH BERBASIS ALKALI AKTIVATOR MATERIAL DILINGKUNGAN GAMBUT - Muhammad Toyeb; Husni Mubarak; Puspa Ningrum; Jefri Gunawan Tanjung (LPPM Universitas Abdurrab, 2023)
Peat water contains low pH and acid caused corrosive on cementation structure as stabilized soil based alkali activated POFA. The soil samples mixed with different percentages of POFA (5%, 10%, and 15%) and alkali activator solution (sodium silica; Na2SiO3) and sodium hydroxide, NaOH) were immersed in peat water for various durations (0, 7, 14, and 28 days). The test results for the physical properties of the soil showed that the addition of POFA decreased the plasticity index and increased the optimum moisture content (OMC) while reducing the dry density (MDD) of the soil mixture. Furthermore, the unconfined compressive strength test indicated that the soil's strength increased at a 5% and 10% POFA content after 7 days of immersion, with strengths of 760 kPa and 1312 kPa, respectively. However, the strength significantly decreased by over 50% after 28 days of immersion, reached 365 kPa and 372 kPa for the respective POFA contents. A slight increase in soil strength was observed with the addition of 15% POFA content during the immersion period. Although the strength obtained after 28 days was almost the same for all mixtures at 356 kPa, higher levels of aluminosilicate synthesis as 15% POFA can enhance the bonding strength between soil particles, making the test specimen more resistant to acid attack.